2017
DOI: 10.3174/ajnr.a5073
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Callosal and Forniceal Diffusion between Patients with and without Postconcussive Migraine

Abstract: BACKGROUND AND PURPOSE: Posttraumatic migraines are common after mild traumatic brain injury. The purpose of this study was to determine if a specific axonal injury pattern underlies posttraumatic migraines after mild traumatic brain injury utilizing Tract-Based Spatial Statistics analysis of diffusion tensor imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…This same association of FA alterations in the fornix-hippocampal pathway and declining verbal memory scores has previously been found in concussed individuals, suggesting that neural networks involving memory are susceptible to injury, and that these alterations in our subjects might be related to repetitive neurotrauma. 24 …”
Section: Discussionmentioning
confidence: 99%
“…This same association of FA alterations in the fornix-hippocampal pathway and declining verbal memory scores has previously been found in concussed individuals, suggesting that neural networks involving memory are susceptible to injury, and that these alterations in our subjects might be related to repetitive neurotrauma. 24 …”
Section: Discussionmentioning
confidence: 99%
“…DTI findings that could be specific for post‐traumatic headache were investigated by comparing patients who had post‐traumatic headache and other postconcussion symptoms to patients who had postconcussion symptoms without headache. Those with post‐traumatic headache had patterns of white matter injury in the corpus callosum and the fornix that differed from those patients without post‐traumatic headache . This is an interesting finding, as white matter diffusion changes in the corpus callosum have also been identified in patients with migraine, and there is some evidence that migraine frequency might modulate white matter integrity in the corpus callosum .…”
Section: Introductionmentioning
confidence: 81%
“…Neuroimaging studies in persistent PTH have been performed to establish the brain structural [37][38][39][40][41] and functional changes [42][43][44][45] that could explain its pathophysiology, these include structural changes of the brain volume and density by voxel-based morphometry [25,37] and brain thickness [38]. The white matter changes were studied by DTI measuring decreased fractional anisotropy, mean diffusivity and radial diffusivity and establishing the fiber tract profiles [24,39]. The gray matter changes in persistent PTH were measured by gray matter volume [40] and voxel-based morphometry [37].…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…The functional changes in the brain associated with persistent PTH were studied using default mode network [42], resting state MRI with static and dynamic functional connectivity [43], perfusion weighted imaging [46], CBF [45] and proton spectroscopy [44]. Some studies compare persistent PTH with healthy controls [25,[37][38][39][40][41][42][43][44][45] and others with migraine patients [24,25,43,45]. The studies that have compared persistent PTH with migraine, found structural [25,38] and functional brain changes [43] between groups, which suggest that migraine and persistent PTH have different pathophysiologic mechanisms.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation